Ontological Relations of the 1945 Basic Act as the Constitution with Pancasila as the State Ideology - Vitanka, Potrika Janno (Berumpun: International Journal of Social, Politics, and Humanities, 2023)
This article discusses the relationship between Pancasila and the UUD 1945 as a constitution and laws, implementing regulations and policies to see its ontological gaps. The discussion focused on the constitutional phenomenon, which must elaborate on constructing the 1945 Basic Act and Pancasila. This article aims to see the dimensions of legal ontology related to the understanding and practice of justice in the country and state. The method used is to apply a content analysis approach, which identifies patterns, themes, or meanings that arise from the concept material contained in Pancasila and the 1945 Basic Act. From this research, ontological problems that need more profound attention are found. Given the overly broad ontological nature, further research is needed to identify more profound problems. This research has significant significance because it can be a marker of problems at the philosophical level that need attention.